EFEKTIVITAS MODEL DISCOVERY LEARNING BERBANTUAN MEDIA PAPECAH TERHADAP KEMAMPUAN PEMAHAMAN KONSEP SISWA KELAS II SDN KARANGJATI 01 - Permata Sari Waruwu, Ade; Hesti Yunitiara Rizqi (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
This study is motivated by the low level of students' conceptual understanding in mathematics, particularly in fraction material at the elementary school level. The purpose of this study is to determine the effectiveness of the discovery learning model assisted by papecah media on students' conceptual understanding ability. The research method used is pre-experimental with a one-group pretest-posttest design. The subjects of this study were 18 second-grade students of SD Negeri 01 Karangjati. Data collection techniques were conducted through tests (pretest and posttest), questionnaires, and observations. The results showed that the average pretest score of 44.3333 increased to 83.6111 in the posttest. The result of the paired sample t-test showed a significance value of 0.000 < 0.05, indicating a significant difference between pretest and posttest results. In addition, the N-Gain score was 0.6948, which falls into the medium category. Therefore, it can be concluded that the discovery learning model assisted by papecah media is effective in improving students' conceptual understanding ability.